Physiological and biomechanical profile of the athletes competing in a world cup cross country ski relay event - Thomas, Mark (My University, 1997)
A variety of studies have been conducted which have attempted to relate biomechanical and physiological variables to cross-country skiing performance. These investigations have taken place in different settings including in the laboratory, outside on roller skis, or on-snow on skis during time trials and competitions. The design of these studies undoubtedly provided the researchers with considerable control over a variety of confounding variables. However, these attempts at controlling variables may have inadvertently created artificial situations with little or no relevance to actual racing situations. Forsberg (1992) pointed out that no one variable can fully account for the observed differences in skiing performance. A more integrated approach to studying the sport was suggested by Hoffman & Clifford (1992) combining physiological and biomechanical measurements in order to achieve a better understanding of which variables affect performance. The primary purpose of this study was to develop a physiological and biomechanical profile of the athletes competing in the free technique legs of the 1994 World Cup Men’s Cross-Country Ski Relay event in Thunder Bay, Ontario, Canada. The secondary purpose was to describe the statistical contributions of specific kinematic and temporal variables to the race velocity of World Cup level cross-country skiers. The tertiary purpose of this study was to compare the top international skiers to the Canadian skiers on the basis of specific physiological and kinematic variables. The study involved the collection of physiological data from six male members of the Canadian National Cross-Country Ski Team four months prior to the relay event and the collection of physiological, biomechanical, and timing study data during the event. Further biomechanical and timing study data were collected from the remaining 18 international competitors in the skating legs of the relay. The lab testing involved V02peak testing and monitoring of heart rates. The race site testing included the monitoring of heart rates during the race, of whole blood lactates immediately before and after the race, of kinematic and temporal analysis of the offset skating technique on a steep uphill, of skating techniques used on different terrain, and of times taken to ski different parts of the race course. The physiological, technique census, and timing study data were analyzed using descriptive statistics. The kinematic and temporal data were analyzed using a combination of descriptive, multiple correlation, and multiple regression statistics. The kinematic and temporal analysis revealed several significant relationships with race velocity. Cycle length was positively correlated with race velocity at the p<.01 level of significance. Cycle velocity and percentage of the full cycle skating on the downhill ski were positively correlated with race velocity at the p<.05 level of significance. Further significant correlations were found among the remaining selected variables. Cycle length was negatively correlated (p<.05 level) with the percentage of the full cycle skating on the downhill ski. Cycle time was negatively correlated (p<.05 level) with the percentage of the full cycle time skating on the uphill ski. Percentage of the full cycle time skating on the uphill ski was negatively correlated (p<.05 level) with percentage of the full cycle time skating on the downhill ski. A multiple regression equation revealed that cycle length was the best predictor of race velocity. The Canadian skiers were found to differ in terms of their physiological and biomechanical profiles as they related to race performance. The physiological analysis of the Canadian subjects revealed several interesting relationships between heart rates and whole blood lactate values and race velocity. The subjects anaerobic thresholds were a good indicator of their relay race performance. The faster subjects raced close to 90 percent of their maximum heart rate. Pre-race and post-race whole blood lactate values were similar to values reported by other studies for top skiers. The peak post-race lactate values did not show any trend in relation to race velocity. However, the fastest subjects had the highest whole blood lactate clearance rates. A comparison of the Canadian subjects on the basis of several kinematic and temporal variables did not show any trends in relation to their race performance. However, a closer look at their skating technique preferences on different terrain showed some variation. The fastest subject preferred to use the 2-skate technique on 1-5 degree slopes, but the other subjects used a combination of the 1-skate, 2-skate, or offset skate techniques. There were some distinct differences between the top skiers and the Canadian skiers in terms of their physiology, skating technique, and mean race velocities for different parts of the race course. The relatively low peak VO2 values for the Canadian skiers compared to previous values reported for top skiers may have set an upper limit to their anaerobic thresholds. The top skiers had higher mean race velocities throughout the course, higher cycle velocities, longer cycle lengths, a more balanced skate off either ski, and a smaller uphill pole angle at the moment of pole plant as compared to the Canadian skiers. The full cycle times and the percentage of the full cycle poling were similar between the two groups. The top skiers preferred to use the 2-skate technique on the 1-5 degree slopes while the Canadians used a variety of techniques. Both groups of skiers used the offset skate on slopes greater than five degrees. The intent of this study was to develop a physiological and biomechancial profile of World Cup level cross-country skiers. Clearly the lack of physiological data on the competitors other than the Canadian subjects limited the inferences that were made regarding the two groups. Despite these limitations this study has revealed some interesting physiological and biomechanical differences between the top skiers and the Canadian skiers. Further studies need to be conducted on the physiological and biomechanical demands of cross-country ski skating on elite level athletes.
Keywords: Cross-country ski racing Physiological aspects; Skiers Physiology; World Cup (Ski racing)